Hubungan antara tekanan kerja dengan self-esteem di kalangan pekerja yang sudah berkahwin di organisasi kerajaan - Rafidah, Suhaili. (Universiti Malaysia Sarawak, UNIMAS, 2008)
The purpose of this research is to study the relation between job stress and self-esteem among married workers in RTM, Kuching Sarawak. This study finds out the correlation between responsibility and workload and also correlation between demographic factor such as gender, age and education level with self-esteem. This study included 54 married workers. There are two instruments had been used in this study. First is the Occupational Stress Inventory Revised Edition (OSI-R) which are used to measure the job stress and the second is Rosenberg Self-Esteem Scale (RSE) which is used to measure the self-es teem. A descriptive statistic method was used to get the frequency and percentage for the demographic factors while Pearson correlation and Spearman correlation was used to test the hypothesis of this research. Results had shown that the gender, age, education level and job stress had no significant correlation with self-esteem.